Successful cardiopulmonary resuscitation of cardiac arrest induced by massive pulmonary embolism under general anesthesia: a case report - Li, Zhen; Cai, Ning (Frontiers in Cardiovascular Medicine, 2023)
Background: While pulmonary embolism (PE) is a common occurrence, a large, life-threatening PE is not. Herein, we discuss a case of life-threatening PE that occurred under general anesthesia. Case presentation: We present the case of a 59-year-old male patient who had been in bed rest for several days due to trauma that resulted in femoral and rib fractures and lung contusion. The patient was scheduled for femoral fracture reduction and internal fixation under general anesthesia. After disinfection and surgical towel laying, severe PE and cardiac arrest suddenly occurred; the patient was successfully resuscitated. Computed tomography pulmonary angiography (CTPA) was performed to confirm the diagnosis, and the patient’s condition improved after thrombolytic therapy. Unfortunately, the patient’s family eventually discontinued treatment. Discussion: Massive PE frequently occurs suddenly, may endanger patient's life at any point in time, and cannot be diagnosed quickly using clinical manifestations. Although the vital signs fluctuate greatly and there is insufficient time to conduct more tests, some factors such as special disease history, electrocardiography, end-tidal carbon dioxide, and blood gas analysis may help us determine the preliminary diagnosis; however, the final diagnosis is made using CTPA. Current treatment options include thrombectomy, thrombolysis, and early anticoagulation, of which thrombolysis and early anticoagulation are the most feasible. Conclusion: Massive PE is a life-threatening disease that requires early diagnosis and timely treatment to save patients' lives.